Preparation and characterization of a novel imidacloprid microcapsule via coating of polydopamine and polyurea. Issue 26 (10th March 2017) - Gao, Zideng; Pang, Long; Feng, Haojie; Wang, Shunyi; Wang, Qiuyun; Wang, Mengyao; Xia, Yining; Hu, Shuwen
Abstract : A novel method to encapsulate imidacloprid with step self-polymerization of dopamine and IPDI was developed, which no organic solvent or surfactant was used in the preparation process. Abstract : Encapsulation of pesticides with polymeric materials is a promising approach to improve the efficacy of pesticide application and reduce the potential risks of pesticides to the environment and humans. In this study, a novel imidacloprid microcapsule was prepared by depositing a polydopamine (PDA) layer on imidacloprid via oxidative self-polymerization followed by a polyurea (PU) layer on PDA via copolymerization. No organic solvent or surfactant was used in the preparation process. The entrapment rate of imidacloprid was determined to be 47.28 ± 0.87%, and the pesticide loading of microcapsule was 68.36 ± 1.13%. Several characterization assays, such as Fourier infrared transform analysis, thermogravimetric analysis and contact angle analysis, were conducted to confirm the encapsulation of imidacloprid. Dynamic light scattering showed that the microcapsule size ranged from hundreds of nm to several μm, which was similar to the results obtained by scanning electron microscopy. The microcapsule had a stable dispersion up to one month in the aqueous solution. Moreover, the microcapsule was able to release imidacloprid in a sustainable manner, as the release was much slower than the non-encapsulated imidacloprid.